The symbolism of marriage in early Christianity and the Latin middle ages : images, impact, cognition - Engh, Line Cecilie (Knowledge communities (Amsterdam, Netherlands), 2019)
In the middle ages everyone, it seems, entered into some form of marriage. Nuns - and even some monks - married the bridegroom Christ. Bishops married their sees. The popes, as vicars of Christ, married the universal church. And lay men, high and low, married carnal woman. What unites these marriages was their common reference to the union of Christ and church. Christ's marriage to the church was the paradigmatic symbol in which all the other forms of union participated - in superior or inferior ways. This book grapples with questions of the impact of marriage symbolism on both ideas and practice in the early Christian and medieval period. In what ways did marriage symbolism - with its embedded concepts of gender, reproduction, household, and hierarchy - shape people's thought about other things, such as celibacy, ecclesial and political relations, and devotional relations? How did symbolic thinking, contrariwise, shape marriage regulation and law? And how, if at all, were these two directions of thinking symbolically about marriage related?